Materials engineering and technologies for production and processing III ICIE-2017, selected and peer reviewed papers from the International Conference on Industrial Engineering, May 16-19, 2017, Saint-Petersburg, Russian Federation /$ceditied by Andrey Radionov - Radionov, Andrey A. (Solid state phenomena, 2017)
The presented collection of scientific papers was created by results of the International Conference on Industrial Engineering (May 16-19, 2017, Saint-Petersburg, Russian Federation). This collection contains results of the latest scientific researches and engineering solutions in the area of the functional and structural materials, technologies of materials processing and innovative technologies in the metallurgical industry. We hope that this book will be useful for the many specialists from these areas of engineering scince